2017
DOI: 10.1038/nphys4156
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence of a new energy scale for superconductivity in H3S

Abstract: The discovery of a superconducting phase in sulfur hydride under high pressure with a critical temperature above 200 K has provided fresh impetus to the search for superconductors at ever higher temperatures. Although this systems displays all the hallmarks of superconductivity, the mechanism through which it arises remains to be determined. Here we provide a first optical spectroscopy study of this superconductor. Experimental results for the optical reflectivity of H 3 S, under hydrostatic pressure of 150 GP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 30 publications
6
92
1
Order By: Relevance
“…This prevents an immediate practical application of hydrogen sulfide, but nonetheless it represents a big leap toward the realization of metallic hydrogen and its room‐temperature superconductivity at high pressure. In particular, a recent optical reflectivity study showed convincing evidence that hydrogen sulfide is a conventional superconductor, with the superconductivity originating from electron–phonon interaction . Theoretical calculation based on the Midgal–Eliashberg theory (an extension of the BCS theory to strong coupling regime) also showed a very good agreement with the experiment in the T c and its temperature dependence.…”
Section: Introductionmentioning
confidence: 77%
“…This prevents an immediate practical application of hydrogen sulfide, but nonetheless it represents a big leap toward the realization of metallic hydrogen and its room‐temperature superconductivity at high pressure. In particular, a recent optical reflectivity study showed convincing evidence that hydrogen sulfide is a conventional superconductor, with the superconductivity originating from electron–phonon interaction . Theoretical calculation based on the Midgal–Eliashberg theory (an extension of the BCS theory to strong coupling regime) also showed a very good agreement with the experiment in the T c and its temperature dependence.…”
Section: Introductionmentioning
confidence: 77%
“…The (1 + λ) mass enhancement shows up in the imaginary part, where it translates to an increased slope at the low-frequency linear regime as well as a strong reduction in the magnitude. These results do not resolve the origin of the feature studied by Capitani et al 35 Summary. We have demonstrated the significant impact of strong electron-phonon coupling on the electron spectral density and band renormalization of the high-temperature superconductor H 3 S, pointing out its relationship with the sharp and asymmetric DOS peak near the Fermi level caused by two neighboring vHs.…”
Section: Effect Of the Superconducting Gapmentioning
confidence: 62%
“…While a general study of the effect of vHs awaits further developments, something can be said about the far infrared where interband transitions are negligible. Capitani et al 35 have reported the observed and modeled reflectivity in H 3 S at high pressure, observing structure identified with an energy scale of 160 meV, suggested to be a phonon with a very strong infrared coupling that is not evident from current theory. Given the paucity of experiments that are possible at high pressure, this experiment assumes unusually strong impact.…”
Section: Effect Of the Superconducting Gapmentioning
confidence: 98%
“…34). Very recently, Capitani et al 35 measured the reflectance of SH 3 at 155 GPa in a diamond anvil cell (DAC) and so probed the electron-phonon interaction in the system establishing a new high energy scale for its superconductivity. These experiments leave no doubt that we are dealing with conventional electron-phonon superconductivity.…”
Section: Introductionmentioning
confidence: 99%